2006
DOI: 10.1158/0008-5472.can-05-3043
|View full text |Cite
|
Sign up to set email alerts
|

IFN-β Is a Highly Potent Inhibitor of Gastroenteropancreatic Neuroendocrine Tumor Cell Growth In vitro

Abstract: IFN-A controls hormone secretion and symptoms in human gastroenteropancreatic neuroendocrine tumors (GEP-NET) but it rarely induces a measurable tumor size reduction. The effect of other type I IFNs, e.g., IFN-B, has not been evaluated. We compared the antitumor effects of IFN-A and IFN-B in BON cells, a functioning human GEP-NET cell line. As determined by quantitative reverse transcription-PCR analysis and immunocytochemistry, BON cells expressed the active type I IFN receptor mRNA and protein (IFNAR-1 and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 48 publications
2
53
0
Order By: Relevance
“…Notwithstanding IFN-␤ half-life (1 h) is shorter than that of IFN-␣ (4 -7 h), several studies showed that IFN-␤ has more potent antitumor effects than IFN-␣, via the activation of apoptosis (6,8,12,16,27,(31)(32)(33). In addition, new strategies could improve in future the pharmacokinetic and pharmacodynamic profile of IFN-␤, like the pegylated formulation (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notwithstanding IFN-␤ half-life (1 h) is shorter than that of IFN-␣ (4 -7 h), several studies showed that IFN-␤ has more potent antitumor effects than IFN-␣, via the activation of apoptosis (6,8,12,16,27,(31)(32)(33). In addition, new strategies could improve in future the pharmacokinetic and pharmacodynamic profile of IFN-␤, like the pegylated formulation (21).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we observed a more potent antiproliferative activity after treatment with IFN-␤ than IFN-␣ in the NET cell line BON. This effect is likely related to the fact that IFN-␣ induced cell cycle arrest only, whereas both apoptosis and a more potent delay in S-G 2 /M phase transit of the cell cycle were responsible for IFN-␤-mediated growth suppression in BON cells (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-a and -b are multifunctional cytokines that have shown efficacy in the treatment in vitro and in vivo of several tumours types including PDAs (Booy et al, 2014;Lindner et al, 1997;Tomimaru et al, 2011;Vitale et al, 2006Vitale et al, , 2007.…”
Section: The Immunostimulatory Activity Of H7n3 Ns1-77 Virus In Infecmentioning
confidence: 99%
“…The reported antitumor activity of IFN-ß exceeds that of IFN-· in several kinds of cancers (25)(26)(27)(28)(29). We compared previously the antitumor of IFN-ß to IFN-· on HCC and reported that IFN-ß had synergistic antitumor effect with anticancer drugs even in HCC cells with weak IFNAR2 expression level (30).…”
Section: Introductionmentioning
confidence: 99%